VD_FINDINFO ML / 2013 / 148 vom 24. Mai 2013 - VD Tribunal cantonal (2013)
TITRE DE MAINLEVÉE, PRÊT DE CONSOMMATION, INTÉRÊT MORATOIRE, DEMEURE DU DÉBITEUR, SOLIDARITÉ | 166 CC, 102 al. 1 CO, 104 al. 1 CO, 143 CO, 82 LP